IDENTIFIKASI KESESUAIAN PENGGUNAAN LAHAN PERTANIAN DAN TINGKAT PENCEMARAN AIR SUNGAI (STUDI KASUS DAS BRANTAS HULU KOTA BATU) - Lusiana, Novia; Rahadi, Bambang; Anugroho, Fajri (Bumi Lestari, 2017)
Development on each sector would gived negatife effect for  environment quality, such as agriculture development to be agroindustry. One of the negative effect of intensification effort through using of pesticide is donate contaminant to water. Identification of suitability agriculture landuse and water polution level by pesticide using is the one effort to save a resource from intensification agriculture efforts. The methods that we was used are analysis spatial for determined of suitability agriculture landuse and contamination indeks for describe how far the water contamination. The result showed that the area where suitable for agriculture in Batu is 1333, 54 Ha or 6,78% and the evaluation result showed there is unsuitable landuse in existing condition is 25,67% from total area, and 32,05% for spatial planning condition. The increased of unsuitable landuse on spatial planning caused by agriculture sector development which the area for agriculture more larger than the land capability, planing for agriculture area is 3289, 76 Ha. Contamination level for water river in Brantas from good condition with IP value is 0.92 on Sumber Brantas and the higest level in Ngujung’s river with IP value is 245,39 with weigh level status. Agriculture intensification efforts also have contribution to reduction water quality on the upper of Brantas.